2020
DOI: 10.1063/5.0012958
|View full text |Cite
|
Sign up to set email alerts
|

On the use of leading-edge serrations for noise control in a tandem airfoil configuration

Abstract: Passive noise control for a tandem NACA 65-710 airfoil configuration is experimentally investigated by applying leading-edge serrations on the rear airfoil. With a sliding side-plate mechanism that allows the rear airfoil to move in the vertical direction relative to the front airfoil, the position of maximum turbulence interaction noise is first identified from the far-field noise measurements. Subsequently, detailed static surface pressure distribution and unsteady surface pressure fluctuations are acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…Similar remote sensing technique and the calibration procedures have been used to study the aerofoil trailing-edge noise in static and dynamic conditions [37,38]. The synchronous measurements were acquired with National Instruments PXIe-4499 data acquisition modules at a sampling rate of 2 16 Hz for 16 seconds and subsequently subjected to Welch function for post-processing to yield the power spectral density (PSD) and sound pressure level (SPL) of the nearfield pressure fluctuations and far-field noise, respectively. With a window size of 2 13 and 50% window overlap, the frequency resolution, i.e.…”
Section: Pressure and Velocity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar remote sensing technique and the calibration procedures have been used to study the aerofoil trailing-edge noise in static and dynamic conditions [37,38]. The synchronous measurements were acquired with National Instruments PXIe-4499 data acquisition modules at a sampling rate of 2 16 Hz for 16 seconds and subsequently subjected to Welch function for post-processing to yield the power spectral density (PSD) and sound pressure level (SPL) of the nearfield pressure fluctuations and far-field noise, respectively. With a window size of 2 13 and 50% window overlap, the frequency resolution, i.e.…”
Section: Pressure and Velocity Measurementsmentioning
confidence: 99%
“…They concluded that altering the relative position of the two aerofoils in tandem led directly to the changes in which the rear aerofoil interacted with the front aerofoil wake and hence, the aerodynamic noise generated during the dynamic interaction. Later, a number of studies have focused on several aspects of the wake-aerofoil interaction phenomenon, such as its aerodynamic performance at low to moderate Reynolds numbers [4,5,6], the interaction noise characteristics and effects of aerofoil geometries [7,8,9,10,11,12] and the reduction of interaction noise using passive control methods [13,14,15,16,17], just to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…the dynamic pressure information is carried to the microphone via plastic tubing. A detailed description of the applied remote sensing method is given by Vemuri et al [31] for a similar configuration. The direct and remote sensing transducers are arranged along the center line of the chord.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…High-lift components, such as slats consisting of broadband and narrowband features in particular, contribute greatly to the airframe noise. Several passive and active flow control methods, such as morphing structures, [1][2][3][4][5][6][7][8] porous materials, [9][10][11][12][13] surface treatments, 14 serrations, [15][16][17][18][19] and transverse jets, 20,21 are being investigated to minimize the overall airframe noise. Despite this, the noise related to the conventional slat and wing configurations remains unresolved.…”
Section: Introductionmentioning
confidence: 99%